VARIASI DIATOM EPIFITIK (BACILLARIOPHYCEAE) PADA BATANG DAN PNEUMATOPHORE BAKAU AVICENNIA SP. DI KAWASAN PELABUHAN TANJUNG BUTON, PROVINSI RIAU - Sofyan H Siregar; Karta S Telaumbanua (Jurnal Ilmu Lingkungan, 2010)
This research was conducted from April-March 2007 in the waters around the PelabuhanTanjung Buton, Riau Province. The aim of this research is to understand the variation of speciescomposition and abundance of epiphytic diatom presenting on the trunk and Pneumatophores ofavicennia sp which is related to water quality factor. Survey method was applied on thisresearch where data were obtained by direct observation in the field. The samples of epiphyticdiatom were analyzed in the Laboratory of Marine Maicrobiology. Water quality parameterswere measured in situ.Twenty Two genus of epiphytic diatom that were consisted of 37 species were found.32 specieswere present on the trunk and 30 species on the Pneumatophores. The abundance of epiphyticdiatom on the trunk ranged from 459 to 10107 ind/cm2 while on the Pneumatophores is from 459 to 9648 ind/cm2. Beside that, water quality parameters were in the sufficient range formarine epilithyc diatom.